Floristic and structure of the arboral community of a regenerating fragment of Atlantic Forest, Igarassu, Pernambuco, Brazil - Andréa Vasconcelos Freitas Pinto; Maria Amanda Menezes Silva; Ana Virginia de Lima Leite; Ladivania Medeiros do Nascimento; Ana Carolina Borges Lins-e-Silva; Maria Jesus Nogueira Rodal (Agro@mbiente On-line, 2018)
Understanding secondary forest structure and functioning is essential for future planning of effective use and/or recompositioning of such areas. The secondary succession process is influenced by the characteristics of componente species, their interaction with other species and with abiotic components. Thus, the objective of the current study was to evaluate the vegetation structure, dispersion syndromes and pollination of a secondary forest fragment with 5 years of regeneration in the Atlantic Forest landscape of Pernambuco, northern Brazil. A total of 30 permanent 10 x 10 m plots with 10 m separations were used for canopy sampling (i.e., all woody individuals with stem diameter at 1.30 m (DBH) greater than 5 cm. Floristic composition analysis recorded 32 species from 21 families. Absolute density was 150 individuals with basal area of 4.787 m² ha-1, and the Shannon-Weaver index (H ‘) was 2.960. The family with the highest number of species was Melastomataceae, while those with greatest abundance were Malpighiaceae (26) and Cecropiaceae (14). Species with the highest Importance Values included Byrsonima sericea (49.28%), Cecropia pachystachya (38.49%) and Bowdichia virgilioides (37.19%). The predominant tree species dispersal syndrome was zoochory (72 species), and the predominant pollination syndrome was melitophilia. Arboreal individuals were mostly recorded in the initial diameter and height classes, indicating that the study area is in the initial stage of succession.